2015
DOI: 10.1073/pnas.1409480112
|View full text |Cite
|
Sign up to set email alerts
|

Visualized macrophage dynamics and significance of S100A8 in obese fat

Abstract: Chronic low-grade inflammation of adipose tissue plays a crucial role in the pathophysiology of obesity. Immunohistological microscopic analysis in obese fat tissue has demonstrated the infiltration of several immune cells such as macrophages, but dynamics of immune cells have not been fully elucidated and clarified. Here, by using intravital multiphoton imaging technique, to our knowledge for the first time, we analyzed and visualized the inflammatory processes in adipose tissue under high-fat and high-sucros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…Our data are consistent with those observed by Sekimoto et al (2012) and Yamaoka et al (2013) [39,40], who found the expression levels of S100A8 , S100A9 , and S100A12 were positively correlated with VAT adiposity in human and overexpression of S100A8 and S100A9 could increase adipose inflammation. Most recently, upregulated S100A8 expression levels were shown to contribute to the very early stage of pathogenesis of obesity and induce local inflammation [41]. Obviously, our data strongly supported that testosterone deficiency with HFC might enhance the risk of inflammation via upregulating the expression levels of inflammatory markers.…”
Section: Discussionsupporting
confidence: 77%
“…Our data are consistent with those observed by Sekimoto et al (2012) and Yamaoka et al (2013) [39,40], who found the expression levels of S100A8 , S100A9 , and S100A12 were positively correlated with VAT adiposity in human and overexpression of S100A8 and S100A9 could increase adipose inflammation. Most recently, upregulated S100A8 expression levels were shown to contribute to the very early stage of pathogenesis of obesity and induce local inflammation [41]. Obviously, our data strongly supported that testosterone deficiency with HFC might enhance the risk of inflammation via upregulating the expression levels of inflammatory markers.…”
Section: Discussionsupporting
confidence: 77%
“…S100A8 and S100A12, belonging to the calgranulin gene family, play key immune response roles in inflammatory disorders, like diabetes and cardiovascular disease [32]. In addition, S100A8 can recruit macrophages to adipose tissue during inflammation and in the setting of hyperglycemia and obesity [33, 34]. It was reported that the elevated expression of TLR8 found in the adipose tissue of patients with obesity or T2D had consensus with inflammatory signatures and may represent an immune marker of metabolic inflammation [35].…”
Section: Discussionmentioning
confidence: 99%
“…MCP1 plays an important role in M1 macrophage recruitment to obese adipose tissue and obesity-associated inflammation (Weisberg et al, 2006). S100A8 was also increased in responders versus non-responders; this gene encodes a damage-associated molecular pattern protein (Sekimoto et al, 2015). The heterodimeric complex of S100A8/S100A9 promotes inflammation by acting as a ligand for TLR4 and is linked to activation of the Nlrp3 inflammasome (Nagareddy et al, 2014).…”
Section: Baseline Characteristics That Separate Responders From Non-rmentioning
confidence: 99%